Increased Risk of Asthma and Allergic Rhinitis in Patients With a Past History of Kawasaki Disease: A Systematic Review and Meta-Analyses - Lei, Wei-Te; Hsu, Chih-Wei; Chen, Po-Cheng; Tseng, Ping-Tao; Kuo, Ho-Chang; Guo, Mindy Ming-Huey; Tu, Yu-Kang; Lin, Pao-Yen; Kao, Yu-Hsuan; Chang, Ling-Sai (Frontiers in Pediatrics, 2021)
Background: Allergic diseases are frequently observed in children with Kawasaki disease (KD). However, the evidence supporting the association between KD and allergies has been conflicting. The objective of the current study is to examine the association between KD and allergic diseases. Methods: We conducted an electronic search using PubMed, Embase, and the Cochrane through 24 July 2021. The inclusion criteria consisted of studies that examined the prevalence of allergic diseases in children with a previous diagnosis of KD and in a comparison group. We pooled studies by using a random effects model. The effects of KD on the subsequent risk of allergic diseases were expressed as odds ratio (OR) with 95% confidence intervals (CI). Results: We included a total of four studies that assessed the effect of KD on asthma, allergic rhinitis, and atopic dermatitis versus non-KD children (KD individuals for asthma, four studies, n = 8474; allergic rhinitis, four studies, n = 8474; atopic dermatitis, three studies, n = 8330). The overall prevalence of asthma, allergic rhinitis, and atopic dermatitis was 9.12%, 27.63%, and 6.55% among patients with previous KD. The meta-analysis showed a significantly increased risk of asthma (OR:1.437, CI: 1.067-1.937) and allergic rhinitis (OR: 1.726, CI: 1.291-2.307) in patients with KD, compared with the control groups. However, patients with KD did not have a significantly different level of risk of atopic dermatitis (OR: 1.243, 95% CI: 0.857-1.802). Conclusion: This meta-analysis supports that individuals with KD are more likely to have asthma and allergic rhinitis compared to controls.